Meningkatkan Kemampuan Kognitif Siswa melalui Model Contextual Teaching and Learning (CTL) Di Kelas VIII MTs Swasta Baharuddin - Rahma Hayati (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2021)
This research purpose to many students are slow to understand the material being tauht, the students is not yet actively expressing his or her opinion, apt to silent, so it is difficult  to know whether or not the students is familiar with the material and teacher learning use the methods of speaking and giving duties to the students later at the end of the assignment and being assembled and inspected by the teacher. So efforts by researchers in resolving the above problem by applying the Contextual Teaching and Learning (CTL) model. This research purpose to know the increasing students cognitive capability through the Contextual Teaching and Learning (CTL) model on linear two-variable equations systems in class VIII MTs private Baharuddin Angkola Muaratais district. This research applied classroom action research (CAR). Classroom action research is discuss process by cycle system. This research done two cycle, every cycle comprise with two meeting. Instrument of collecting date are test and observation. The study subject was class VIII MTs private Baharuddin in 2020/2021 year of 34 students 19 sons and 15 daughters. Studies show that the first test of the completed number of students is 6 people at 17,65%. After application of the Contextual Teaching and Learning (CTL) model there is an increase in the students’ cognitive abilities at each meeting. In the first cycle of the first meeting the average completed of students by 69,67 with the percentage of completeness of 32,35%, the first cycle of the second meeting the average completed of students by 76,88 with the percentage of completeness of 50%, in the second cycle of the first meeting the average completed of students by 83,15 with the percentage of completeness of 70,59%, the second cycle of the second meeting the average completed of students by 90,09 with the percentage of completeness of 85,29%. The students target of achievement is 75%, then this research can be terminated. So it could be concluded that students’ cognitive abilities could increase through a Contextual Teaching and Learning (CTL) model on linear two-variable equations systems in class VIII MTs private Baharuddin Angkola Muaratais district.